Corruption and the Composition of Foreign Direct Investment : Firm-Level Evidence - Smarzynska, Beata K.; Wei, Shang-Jin (World Bank, Washington, DC, 2014)
The authors study the impact of corruption in a host country on foreign investors' preference for a joint venture, or a wholly owned subsidiary. Their simple model highlights a basic tradeoff in using local partners. On the one hand, corruption makes the local bureaucracy less transparent, and increases the value of using a local partner to cut through the bureaucratic maze. On the other hand, corruption decreases the effective protection of an investors' intangible assets, and reduces the probability that disputes between foreign and domestic partners, will be adjudicated fairly, which reduces the value of having a local partner. As the investor's technological sophistication increases, so does the importance of protecting intangible assets, which tilts the preference away from joint ventures in a corrupt country. Empirical tests of this hypothesis on firm-level data show that corruption reduces inward foreign direct investment, and shifts the ownership structure toward joint ventures. Conditional on foreign direct investment taking place, an increase in corruption from the level found in Hungary to that found in Azerbaijan, decreases the probability of a wholly owned subsidiary by 10 to 20 percent. Technologically more advanced firms are less likely to engage in joint ventures, however. The authors find support for the view that U.S. firms are more averse to joint ventures in corrupt countries than other foreign investors - possibly because the U.S. Foreign corrupt Practices Act, which stipulates penalties for executives of U.S. companies whose employees, or local partners engage in paying bribes. But although U.S. companies are more likely than investors from other countries to retain full ownership of firms in corrupt countries, they are not less likely than firms from other countries to undertake foreign direct investment in those countries.